EKSPRESI KESANTUNAN BERBAHASA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMP MUHAMMADIYAH GATAK - Kurnia Cahyaning Putri; Sarwiji Suwandi; Slamet Mulyono (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This Analysis explain and describe 1) the form of politeness and impoliteness of language in Indonesian Language learning activities in SMP Muhammadiyah Gatak, 2) language politeness markers that exist in the form of speech acts in learning Indonesian in SMP Muhammadiyah Gatak, 3) Marks of language disloyalty in Indonesian language learning in SMP Muhammadiyah  Gatak. and (4) the causes of violations of the politeness of language principles in speech acts during Indonesian Language learning. This research is a qualitative descriptive research with source data from act of speech that occurred during the Indonesian language learning took place SMP Muhammadiyah Gatak, Sukoharjo. Sampling technique of this research using purposive sampling. Technique of data validity test that used is triangulation data source and triangulation theory.The results of this research are 1) 296 politeness speeches found, obey the taxt maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim, 2) 48 disloyalty speeches found, breaking taxt maxim, generosity maxim, and modesty maxim, 3) Marks of politeness found that ask and appeal to partner of speak without coercion and not offensive; beg the partner of speak without coercion and not offensive; also has responded positively to the partner of speak; 4) Marks of disloyalty found that critizing by using negatif diction intonation and unable to control emotions; opinion with an offensive opinion to partner of speak; and also cut off tge conversation with partner of speak.